2006
DOI: 10.1038/nrn1928
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signalling in neuron–glia interactions

Abstract: Activity-dependent release of ATP from synapses, axons and glia activates purinergic membrane receptors that modulate intracellular calcium and cyclic AMP. This enables glia to detect neural activity and communicate among other glial cells by releasing ATP through membrane channels and vesicles. Through purinergic signalling, impulse activity regulates glial proliferation, motility, survival, differentiation and myelination, and facilitates interactions between neurons, and vascular and immune system cells. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
665
4
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 748 publications
(699 citation statements)
references
References 165 publications
(15 reference statements)
11
665
4
4
Order By: Relevance
“…The importance of astrocytes and morphological contacts formed between astrocytic processes and synapses is apparent as astrocytes and astrocyte-conditioned media promote synapse formation (Pfrieger and Barres, 1997;Ullian et al, 2001) and both LTP and LTD are affected by astrocytes acting through several mechanisms. Astrocytes directly regulate NMDA-receptor-dependent LTP and plasticity through glial-derived D-serine (Yang et al, 2003;Panatier et al, 2006), ATP and adenosine (Pascual et al, 2005;Fields and Burnstock, 2006), glutamate reuptake and release (Haydon and Carmignoto, 2006) and extracellular K + handling (Wallraff et al, 2006;Djukic et al, 2007;Ge and Duan, 2007). Our findings on activity-dependent astrocyte differentiation by ATP and LIF in vitro and the observation of behavioral impairments in LIF −/− mice (Pechnick et al, 2004) and LIF over-expressing mice (Pechnick et al, 2004) suggest that LIF may be important in hippocampal development and plasticity in vivo through astrocytes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The importance of astrocytes and morphological contacts formed between astrocytic processes and synapses is apparent as astrocytes and astrocyte-conditioned media promote synapse formation (Pfrieger and Barres, 1997;Ullian et al, 2001) and both LTP and LTD are affected by astrocytes acting through several mechanisms. Astrocytes directly regulate NMDA-receptor-dependent LTP and plasticity through glial-derived D-serine (Yang et al, 2003;Panatier et al, 2006), ATP and adenosine (Pascual et al, 2005;Fields and Burnstock, 2006), glutamate reuptake and release (Haydon and Carmignoto, 2006) and extracellular K + handling (Wallraff et al, 2006;Djukic et al, 2007;Ge and Duan, 2007). Our findings on activity-dependent astrocyte differentiation by ATP and LIF in vitro and the observation of behavioral impairments in LIF −/− mice (Pechnick et al, 2004) and LIF over-expressing mice (Pechnick et al, 2004) suggest that LIF may be important in hippocampal development and plasticity in vivo through astrocytes.…”
Section: Discussionmentioning
confidence: 60%
“…We therefore sought to identify the cellular signaling mechanism responsible for activity-dependent regulation of glial development in hippocampus. Although many growth factors could be released in an activitydependent manner from neurons to affect glial development, purinergic signaling has recently become appreciated as an important component of activity-dependent neuron-glial signaling (Fields and Stevens, 2000;Fields and Burnstock, 2006;North and Verkhratsky, 2006). In other contexts, previous research has shown that purinergic signaling through P 2 Y receptors on astrocytes increases the expression and release of LIF (Ishibashi et al, 2006).…”
Section: Spontaneous Neuronal Impulse Activity Regulates Glial Differmentioning
confidence: 99%
“…Purinergic signalling plays an important role in mediating neuron-glia interactions (Fields and Burnstock, 2006;Halassa et al, 2007). In particular, astrocytes play a key role in regulating synaptic levels of adenosine -and thus in the modulation of neuronal activity -based on astrocyte-mediated release of the adenosine precursor ATP (Pascual et al, 2005;Haydon and Carmignoto, 2006), and based on ADK-driven reuptake of adenosine into astrocytes (Boison, 2006;, 2007b;2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Most cells in the brain, including neurons and astrocytes, can release ATP via regulated vesicular transport (Fields and Burnstock, 2006). Extracellular ATP is then cleaved into adenosine by a cascade of ectonucleotidases (Cunha, 2001;Zimmermann, 2000).…”
Section: Presynaptic Vesicular Release Of Atpmentioning
confidence: 99%